The effects of low sulfated ash, phosphorus and sulfur oils on camshaft/tappet tribocouples with various diamond‐like‐carbon coated tappets in motored and fired engines. (11th March 2014) - Durham, John; Kidson, Adam
ABSTRACT This work was conducted as part of an EU FP‐7 project 'Tailoring of Tribological Interfaces for Clean and Energy‐Efficient Diesel and Gasoline Powertrains'. The primary goal of this work is to reduce fuel consumption in internal combustion engines by the use of bespoke surface coatings and lubricants. Earlier work within the project had defined a series of oils and coatings to be evaluated in the final stage of the project. The results reported in this paper have used the OM646LA engine to evaluate wear and a motored cylinder head manufactured from the same engine type to evaluate the friction performance of coating/oil combinations. The coatings were applied to the tappets in the valvetrain and tested against uncoated camshafts. It will be shown that diamond‐like‐carbons can offer frictional benefits over an all‐steel system and that the choice of lubricant can incrementally reduce friction further. It will also be shown that while some diamond‐like‐carbon coatings are durable enough to survive the fired engine test intact, others are completely removed; interestingly, in all cases, the wear on the counter‐surface, the cam lobes, was in the order of a magnitude lower than for the standard all‐steel system. Copyright © 2014 John Wiley & Sons, Ltd.